1997
DOI: 10.1176/ajp.154.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alzheimer's disease severity on cerebrospinal fluid norepinephrine concentration

Abstract: Despite the loss of locus ceruleus neurons in Alzheimer's disease, the aging-associated high concentration of CSF norepinephrine is retained in the earlier stages of Alzheimer's disease and increases further as the disease progresses. Increased brain noradrenergic activity may contribute to the agitated behaviors or cognitive deficits of patients with advanced Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Noradrenergic function seems to be enhanced in older relative to young adults (Elrod et al, 1997; Raskind et al, 1999), which may mask the differences between both conditions (novel vs. standard) in this age group.…”
Section: Discussionmentioning
confidence: 98%
“…Noradrenergic function seems to be enhanced in older relative to young adults (Elrod et al, 1997; Raskind et al, 1999), which may mask the differences between both conditions (novel vs. standard) in this age group.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, a number of studies have shown no change in norepinephrine levels in different brain regions or cerebrospinal fluid (CSF) in both sporadic and familial AD cases (Sparks et al, 1988; Herregodts et al, 1989; Tohgi et al, 1992). In addition, increased norepinephrine levels were reported, which correlated with decreased cognitive function (Tohgi et al, 1992) and aging (Elrod et al, 1997) in AD patients.…”
Section: Noradrenergic Changes In Admentioning
confidence: 99%
“…Particularly interesting are studies in postmortem AD brains which identified compensatory mechanisms in surviving neurons of the LC network by means of upregulated synthesis of NE and/or a reduced reuptake of the neurotransmitter at the synaptic terminals [79]. This upregulation could explain the unexpected increase of NE levels in cerebrospinal fluid in AD patients with marked LC pathology [80,81]. …”
Section: Locus Coeruleus and The Norepinephrine Systemmentioning
confidence: 99%